Impacts of the global financial crisis on small and medium enterprises in the People's Republic of China - Xiangfeng Liu (Asian Development Bank Institute (ADBI), 2009)
This paper conducts an in-depth analysis of the impacts of the global financial crisis on the People's Republic of China's (PRC's) small and medium enterprises (SMEs). It also provides relevant policy suggestions at the end. First, this paper reviews the impacts of the 1997 Asian financial crisis on the PRC's SMEs, evaluating the policy measures for coping with the crisis at that time and summarizing the relevant experiences. Second, it analyzes the impacts of the current global financial crisis on the PRC's SMEs, focusing the discussion on the causes of and resulting problems from SME' shrinking export markets via reduced export orders, rising operating costs, decreased efficiency, increased shutdowns, sharply rising unemployment, weakened investment confidence, broken lines of funding, and reduced resources. Third, the paper makes a preliminary analysis of the countermeasures taken by the government of the PRC, focusing on its support policies for SMEs and the problems exhibited in the implementation of those policies. Finally, the author makes policy suggestions for boosting the development of SMEs and puts forward relevant measures in the context of an SME credit guarantee, the expansion of financing institutions and channels, tax reductions, the improvement of service systems, and strengthening SMEs' self-construction mechanisms.
Keywords: F14; F41; O11; O20; 330; Finanzmarktkrise; Asien; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Klein- und Mittelunternehmen; China